2011
DOI: 10.1016/j.apm.2010.11.007
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cyclone inlet dimensions on the flow pattern and performance

Abstract: a b s t r a c tThe effect of the cyclone inlet dimensions on the performance and flow field pattern has been investigated computationally using the Reynolds stress turbulence model (RSM) for five cyclone separators. The results show that, the maximum tangential velocity in the cyclone decreases with increasing the cyclone inlet dimensions. No acceleration occurs in the cyclone space (the maximum tangential velocity is nearly constant throughout the cyclone). Increasing the cyclone inlet dimensions decreases th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
97
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 318 publications
(114 citation statements)
references
References 52 publications
(60 reference statements)
1
97
0
1
Order By: Relevance
“…US 325521) was granted to John M. Finch of the United States back in 1885 and assigned to the Knickerbocker Company (Hoffmann and Stein, 2008). In Europe the first exemplify, Elsayed and Lacor (2011a) showed that, increasing the inlet dimensions decreases the maximum tangential velocity in the cyclone and pressure drop and increases the cyclone cut-off diameter. They found that the effect of changing the inlet width is more significant than the inlet height especially for the cut-off diameter and the optimum ratio of inlet width b to inlet height a is somewhere between 0.5 and 0.7.…”
Section: Introductionmentioning
confidence: 98%
“…US 325521) was granted to John M. Finch of the United States back in 1885 and assigned to the Knickerbocker Company (Hoffmann and Stein, 2008). In Europe the first exemplify, Elsayed and Lacor (2011a) showed that, increasing the inlet dimensions decreases the maximum tangential velocity in the cyclone and pressure drop and increases the cyclone cut-off diameter. They found that the effect of changing the inlet width is more significant than the inlet height especially for the cut-off diameter and the optimum ratio of inlet width b to inlet height a is somewhere between 0.5 and 0.7.…”
Section: Introductionmentioning
confidence: 98%
“…In this work, separation efficiency and velocity fields of the cyclone with different inlet velocity were numerically simulated using FLUENT 6.3.26 computational fluid dynamics (CFD) software. Some works of simulation of cyclone using the Reynolds stress model (RSM) have been reported to be suitable for modeling the flow in the cyclone in recent years (Safikhani et al, 2010;Elsayed et al, 2011;Qiu et al, 2012). Therefore, the Reynolds stress model (RSM) of the cyclone internal turbulent flow simulation is used in this paper.…”
Section: Simulationmentioning
confidence: 99%
“…In this work, velocity fields of the cyclone with different feeding flow rate were numerically simulated using FLUENT computational fluid dynamics (CFD) software. Some works of simulation of cyclone using the Reynolds stress model (RSM) have been reported to be suitable for modeling the flow in the cyclone in recent years [13][14][15]. Therefore, the Reynolds stress model (RSM) of the cyclone internal turbulent flow simulation is used in this paper.…”
Section: Modelmentioning
confidence: 99%